Chemical disinfectants and antiseptics. Quantitative test for the evaluation of bactericidal and yeasticidal and/or fungicidal activity of chemical disinfectants in the medical area on non-porous surfaces without mechanical action. Test method and requirements (phase 2, step 2). (18th August 2021) - British Standards Institution,
No abstract available